Storytelling Training in Forming of Child Character at Cambridge Binjai Kindergarten - Widayati, Dwi; Nasution, Ikhwanuddin; Gustianingsih; Lubis, Rosliana; Lubis, Haris Sutan (Talenta Publisher, 2023)
This storytelling training is based on concern and awareness of the importance of character education in children. Through storytelling, it is hoped that it will be able to shape the character of children for the sake of creating a generation that has strong character to manage and advance the country in the future. Telling stories can be a way of communicating to children. In general, children prefer educational models that are interactive. The partner in this service is the Principal of Cambridge Binjai Kindergarten. The participants, namely Cambridge Binjai Kindergarten students, participated in this training with joy. After this training the students can retell the stories they heard or watched. The results of this training are that it has 1) trained kindergarten children's absorption or comprehension power, 2) trained children's thinking power, 3) trained kindergarten children's concentration power, 4) Developed children's imagination, 5) Created joyful situations and developed an atmosphere of intimate relationships according to the stage of its development, 6) Helping children's language development in communicating effectively and efficiently so that the conversation process becomes communicative. At the end of this activity it is also hoped that a story-telling community will be formed with the name â€œHouse of Storiesâ€ which is managed by the teachers of the Cambridge Binjai Kindergarten. This group was made a pioneer in the movement to cultivate storytelling to educate the character of children at Cambridge Binjai Kindergarten in particular and children in Binjai in general.